Specifications for the erection and completion of a city hall at X - Evans, Earl Joy (My University, 1906)
Introduction: The Drawings referred to in this specification are made to a scale of 1/8 inch = I foot, and are supplemented by detail drawings of a larger scale. Further detail drawings will be furnished as the work progresses. All these drawings are intended to cooperate with this specification, to form a part thereof, and also form part of the contract. When figures are given, they are to be taken in preference to measurement by scale. The drawings and specifications furnished for this work are the property of the architect, and are to be returned to him on the completion of the work. The contractor shall give his personal superintendence to the work and furnish all materials, transportation, labor, scaffolding and appliances required for the full performance of the work herein specified, except as may be otherwise definitely stated. He shall lay out his work and be responsible for its correctness; and shall not sublet any part of this work without the written consent of the building committee or architect. He shall obtain all the necessary permits, paying the lawful fees charged therefor; shall be liable for all accidents to persons or damage to property, traceable to the negligence of himself or his subordinates, and shall be responsible for any violation of local laws or ordinances. He shall adequately protect his work at all time during its progress. All materials employed are, unless otherwise specified, to be the best of their kind and subject to the approval of the building committee and architect. All labor is to be performed in the best and most acceptable manner by skilled workmen, and both workmen and workmanship are subject to the approval of the architect.
Citation: Evans, Earl Joy. Specifications for the erection and completion of a city hall at X. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Architecture; City Hall; Construction; Buildings; Theses